2009
DOI: 10.1177/175045890901900803
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Communication

Abstract: This article has raised the issue of effective communication within the perioperative setting. There are many methods for sending information from one person to another. Most important in effective communication is the clarity of the message and how practitioners check that the recipient understands the intended point. If key aspects in the communication process are not fully understood or utilised, then we subject our patient and our colleagues to potential risk. If poor communication causes untoward and unac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Effective communication involves listening, questioning, and assessing the degree of understanding of the transmitted information. Problems in any of these components can result in defective communication [ 15 ]. In our study, we found the lowest mean scores for the items “checked to be sure I understood everything” (1.9 ± 0.9), “discussed next steps” 2.0 ± 0.9, and “Encouraged me to ask questions” 2.1 ± 1.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective communication involves listening, questioning, and assessing the degree of understanding of the transmitted information. Problems in any of these components can result in defective communication [ 15 ]. In our study, we found the lowest mean scores for the items “checked to be sure I understood everything” (1.9 ± 0.9), “discussed next steps” 2.0 ± 0.9, and “Encouraged me to ask questions” 2.1 ± 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…A number of barriers and challenges have been identified for communication in healthcare [ 1 , 5 , 11 18 ]. Therefore; variety of approaches and models of communication have been proposed and implemented to facilitate optimal communication and interactions between patients and health professionals [ 2 , 3 , 5 , 7 , 15 , 17 , 19 24 ]. However, communication problems have been persisting challenges of clinical practice and multiple barriers has been identified [ 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in improving OR-PACU handovers and evidence shows that interventions directed towards improving handovers enhance teamwork, team effectiveness and efficiency (Siddiqui et al, 2012;Segall et al, 2012). There is a large body of research exploring communication, effective teamwork and interprofessional collaboration within the perioperative environment to enhance safe and efficient care to the surgical patient (Huang, Kim, & Berry, 2013;Healey, Undre, Sevdalis, Koutantji, & Vincent, 2006;Lingard, Reznick, Espin, Regher, & DeVito, 2002;Lingard, Regehr, Espin, & Whyte, 2006;Lingard et al, 2008;Smith & Jones, 2009). There are also initiatives that have been implemented within the operating room to improve patient safety by standardizing the communication process, such as the World Health Organization (WHO) Surgical Safety Checklist (2009).…”
Section: Introductionmentioning
confidence: 99%